Disseminated Superficial Actinic Porokeratosis on the Face Treated with Imiquimod 5% Cream - Hassan Riad; Khaled Mansour; Hussein Al Sada; Samya Abu Shaika; Hamda Al Ansari; Haya Al Mohannadi (Karger Publishers, 2013)
Porokeratoses are a group of hereditary or acquired disorders characterized by annular lesions with an atrophic center and a prominent peripheral ridge. Pathologically, porokeratosis is characterized by the presence of abnormal clones of keratinocytes that form a column of parakeratotic cells, called the cornoid lamella. Fifteen percent of patients of disseminated superficial actinic porokeratosis (DSAP) have facial lesions; other regions like the extensor surface of extremities constitute the majority of reported cases. Exclusively facial lesions are probably less frequent. Rarely, actinic porokeratosis is confined to the nose only. Of reported porokeratosis cases, 7.5% have revealed a malignancy arising within the lesion. We present a case of facial sporadic DSAP that was treated with imiquimod 5% cream in conjunction with a regular sunscreen. Follow-up of this case is important to rule out the possibility of malignant transformation of the lesions.